2018
DOI: 10.1002/mrd.23087
|View full text |Cite
|
Sign up to set email alerts
|

Uterine RGS2 expression is regulated by exogenous estrogen and progesterone in ovariectomized mice, and downregulation of RGS2 expression in artificial decidualized ESCs inhibits trophoblast spreading in vitro

Abstract: Embryo implantation is a complicated event that relies on two critical factors: the competent blastocyst and the receptive uterus. Successful implantation results from tight coordination of these two factors. The maternal hormone environment of the uterus and molecular cross‐talk between the embryo and uterine tissue play pivotal roles in implantation. Here we showed that regulator of G‐protein signaling 2 (RGS2), a member of ubiquitous family of proteins that regulate G‐protein activation, plays an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
(68 reference statements)
1
5
0
Order By: Relevance
“…Additional genes with known roles in decidualization and implantation were dual specificity phosphatase 1 ( DUSP1 ), EGR1 , integrin subunit beta 8 ( ITGB8 ), and norrin cystine knot growth factor NDP ( NDP ) 76 79 . In agreement with the very late and non-invasive implantation in the mare, many genes known to have negative effects on decidualization and invasive implantation were found as upregulated in LE of pregnant compared to cyclic mares, e.g., parathyroid hormone-hike hormone ( PTHLH ) 80 , regulator of G protein signaling 2 ( RGS2 ) 81 , and tissue inhibitor of metalloproteinases-3 ( TIMP3 ) 82 .…”
Section: Discussionsupporting
confidence: 63%
“…Additional genes with known roles in decidualization and implantation were dual specificity phosphatase 1 ( DUSP1 ), EGR1 , integrin subunit beta 8 ( ITGB8 ), and norrin cystine knot growth factor NDP ( NDP ) 76 79 . In agreement with the very late and non-invasive implantation in the mare, many genes known to have negative effects on decidualization and invasive implantation were found as upregulated in LE of pregnant compared to cyclic mares, e.g., parathyroid hormone-hike hormone ( PTHLH ) 80 , regulator of G protein signaling 2 ( RGS2 ) 81 , and tissue inhibitor of metalloproteinases-3 ( TIMP3 ) 82 .…”
Section: Discussionsupporting
confidence: 63%
“…In the parallel endometrium study, RGS2 was found as upregulated in LE of pregnant compared to cyclic mares at later stages 12 . This gene has been associated with negative effects on decidualization and invasive implantation, linked to the very late and non-invasive implantation in the mare 65 . On the miRNA level, it is noteworthy that 6 out of the 15 DA miRNAs were increased at day 10 compared to the other days p.o.…”
Section: Discussionmentioning
confidence: 99%
“…The mice were raised under a 12 h light/dark cycle under specific pathogen-free conditions with 55–65% relative humidity at 22–24°C, and were allowed free access to water and standard rodent chow. Mice were ovariectomized (OVX) under general anesthesia, as described previously [ 38 ], and were kept individually for two weeks for complete recovery. The mice were then regrouped again, and 60 mice were randomly divided into six groups with 10 mice in each group: (1) The E 2 group: OVX mice received daily intraperitoneal (IP) injections of corn oil containing E 2 (100 ng of E 2 in 100 μL of corn oil/mouse, E2758, Sigma-Aldrich, St. Louis, MO, USA) at 8:30 a.m. for 3 days [ 39 ].…”
Section: Methodsmentioning
confidence: 99%
“…2835, Tocris Bioscience, Bristol, UK) at 8:30 a.m. for 3 consecutive days [ 40 ]. (3) The E 2 + P 4 group: OVX mice received daily IP injection of E 2 (100 ng of E 2 in 100 μL of corn oil/mouse) at 8:30 a.m. for 2 days, and then were treated with P 4 (1 mg of P 4 in 100 μL of corn oil/mouse) by IP injection at 8:30 a.m. on the 3rd day [ 38 ]. (4) The ICI 182780 group: female mice with intact ovaries received IP injection of ICI 182780 (an estrogen receptor antagonist, 100 μg/mouse, Cat.…”
Section: Methodsmentioning
confidence: 99%